Sistem Pemilihan Paket Indihome Dengan Metode Topsis - Fariz Budianto Candra; David David (Jurnal Informatika dan Komputer, 2022)
t is necessary to create a system to make it easier for prospective customers to make decisions to choose a package that suits their needs, so there is a need for criteria to assist in the selection of the IndiHome package. The software development methodused is the prototype method. The test method used in writing this research is black box testing. The results showed that the main reason for designing a decision support system for selecting the IndiHome package was a problem that often occurred to consumers when choosing an internet package that did not suit their needs and lack of information. IndiHome package selection decision support system software using the resulting TOPSIS method can support decision-making for users who use it. Various parties can use this software in choosing the IndiHome package to provide convenience in supporting decisions before buying the package. The software has been designed with static and dynamic properties. In terms of interface, this application is only static becausethe user can only input data according to what has been provided. Suggestions from the conclusions that can be given are that this software can be developed using other programming languages such as Java or Python to make repairs and development more accessible and immediately acceptable to users.